Análise de metilação de DNA nos genes da citoqueratina 14 (KRT14) e 19 (KRT19) em amostras de pele exposta e não exposta ao sol - Barroso, Haline (2015)
It is well established that solar UV radiation can cause mutations in DNA and increase the risk of developing skin cancer. However, little is known about the ability of UV radiation to cause epigenetic changes in the skin. DNA methylation, characterised by the addition of a methyl group in cytosines within CpG dinucleotides, can modify gene transcription, leading to decreased expression or even silencing of a gene. Epigenetic changes could represent an important pathway by which environmental factors influence aging and disease risks, with a tissue-specific manner. Epithelial keratins are called cytokeratins, the main function of cytokeratins is to maintain the integrity and mechanical stability through cell-cell contacts with epithelial tissue. The aim of this study was to investigate the sun exposure influence on DNA methylation status in the cytokeratin 14 (KRT14) and 19 (KRT19) genes of skin cells of subjects whithout history of skin disease. Skin biopsies were obtained by punch of sun-exposed (outer forearm) and sun-protected areas (inner arm) from 30 corpses of the Brazilian Services of Death Investigation. The KRT14 gene DNA methylation analysis was performed using Methylation-Specific PCR (MSP), and the KRT19 gene DNA methylation analysis was performed using Methylation-Sensitive Restriction Enzymes (MSRE) of sun-exposed and sun-protected skin areas. Statistical analysis showed no significant differences between sun-protected and sun-exposed areas and the most frequently methylated condition for CpG studied for KRT14 and KRT19 genes (p> 0.05; McNemar). We conclude that sun exposure does not induce changes in DNA methylation status in the KRT14 and KRT19 genes.